E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 128 (1868); N.Y. Col. MSS, XI. 53, 54 - (:unkn) unknown (My University, 1652)
Prohibited sale of powder, lead, and guns. The exact text is lost but the intention is to restrict sale of arms, especially ammunition, "to the Indians."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES